Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Pegawai Pada BKPSDM Kota Banjar - Oktavia, Dina Nur; Lestari, Suci Putri; Sutrisna, Arga (PT Maju Malaqbi Makkarana, 2023)
This research aims to determine the effect of Training and Work Discipline on the Performance of Banjar City BKPSDM Employees. In this research, the three variables use an ordinal measuring scale. The method used is descriptive verification with a quantitative approach. The sampling technique used is based on the saturated sampling technique. The object of this research is the performance of Banjar City BKPSDM employees as many as 45 respondents. The analytical tool used is multiple linear regression. The results of this study indicate that simultaneous and partial training has a significant effect, but partial work discipline testing has a significant effect on the Performance of BKPSDM Employees in Banjar City.